REGULASI EMOSI DAN PENGAMBILAN KEPUTUSAN PADA PENDAKI GUNUNG - Dewi Nurrahmah Sifa I; Jayaning SIla Astuti (LPPM University 17 Agustus 1945 Samarinda, 2022)
Thereby, public interest in climbing the mountain increase. This study aims to determine the relationship between emotion regulation and decision-making to climb mountains in East Java. The approach that is used in this study is a quantitative approach with purposive sampling technique. The criteria for the subjects in this study are climbers who had climbed mountains in East Java, aged between 13-65 years and wished to reach the top with a total of 349 subjects. The hypothesis in this study are the relationship between emotional regulation and decision-making to climb mountains in East Java. The results of this study obtained a correlation coefficient of 0.657 with a significance of 0.00 (<0.05). So that the hypothesis has been accepted and can be interpreted that emotion regulation and decision making have a positive or unidirectional relationship. So that if the emotional regulation of climbers increases, the accuracy of decision making by climbers will also increase. Conversely, if the emotional regulation of climbers decreases, the accuracy of decision making by climbers will also decrease. The relationship between emotion regulation and decision making is in the strong category, so that further researchers need to link other variables that have a very strong relationship with decision making to see what factors make the biggest contribution when someone makes a decision.Keywords: emotion regulation, decision making, climber